Regional Innovative Trend Analysis of Annual and Seasonal Discharges of Rivers in Bosnia and Herzegovina - Marko Šrajbek; Bojan Đurin; Slobodan Gnjato; Tatjana Popov (Earth, 2025)
Climate change is becoming more pronounced and affecting all environmental components, leading to river flow changes. This study aimed to investigate the annual and seasonal discharge trends for six rivers in Bosnia and Herzegovina in Europe in the period from 1961 to 2020. The trends were analysed using a linear regression (LR) analysis, the Mann–Kendal test (MK), and an innovative trend analysis (ITA). The fewest significant trends were obtained by the LR analysis, followed by the MK test, and the most were obtained by the ITA method. The ITA method identified 76.67% significant negative trends and 13.33% significant positive trends in all data groups. It can be concluded that the discharges in the second part of the observed period (1991–2020) were significantly lower compared to the first part (1961–1990). A more detailed ITA of the flow by data group (low, medium, and high) was also carried out. The results showed the occurrence of increasingly large extremes. Therefore, in the second subperiod, the minimum values were smaller and the maximum values were larger than in the first subperiod. The occurrence of high water levels increases the possibility of floods, and a long dry period can cause problems with the generation of electricity from hydropower plants. For this reason, analysing discharge trends in the future is certainly a justified recommendation.